How to read the Bible for all its worth : a guide to understanding the Bible - Fee, Gordon D; Stuart, Douglas K (Secunderabad, OM Books, 2001)
The believing scholar insists that the biblical texts first of all mean what they meant. That is, we believe that God's Word for us today is first of all precisely what his Word was to them. Thus we have two tasks: first, to find out what the text originally meant; this task is called exegesis. Second, we must learn to hear that same meaning in the variety of new or different contexts of our own day; we call this second task hermeneutics. In its classical usage, the term "hermeneutics" covers both tasks, but in this book we consistently use it only in this narrower sense. To do both tasks well should be the goal of Bible study. - Preface
1.Introduction: The Need to Interpret --2.The Basic Tool: A Good Translation --3.The Epistles: Learning to Think Contextually --4.The Epistles: The Hermeneutical Questions --5.The Old Testament Narratives: Their Proper Use --6.Acts: The Question of Historical Precedent --7.The Gospels: One Story, Many Dimensions --8.The Parables: Do You Get the Point? --9.The Law(s): Covenant Stipulations for Israel --10.The Prophets: Enforcing the Covenant in Israel --11.The Psalms: Israel's Prayers and Ours --12.Wisdom: Then and Now --13.The Revelation: Images of Judgment and Hope --Appendix: The Evaluation and Use of Commentaries
Includes bibliographical references (pages 249-254) and indexes
Keywords: Bible -- Study and teaching